1986
DOI: 10.7326/0003-4819-105-6-829
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Value of Two-Dimensional Exercise Echocardiography to Routine Treadmill Exercise Testing

Abstract: Two-dimensional echocardiograms were done during rest and after exercise in 95 patients who subsequently had coronary arteriography. Prior myocardial infarction was present in 36 patients, 35 of whom had wall motion abnormalities. There was no evidence of prior infarction in 59 patients, 44 of whom had coronary disease. In these 44 patients, the exercise electrocardiogram showed ischemia in 19, was normal in 13, and was nondiagnostic in 12. Exercise echocardiograms were abnormal in 35 of these 44 patients. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(27 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Dobutamine was infused intravenously using a mechanical pump, starting at the dose of 5 jig/kg per minute for 3 minutes, increasing by 5 ug/kg per minute at 3-minute intervals to a maximal rate of 40 ,ug/kg per minute administered over 5 minutes. Dipyridamole was infused intravenously at the dose of 0.56 mg/kg over 4 minutes, followed by 4 …”
Section: Stress Protocolsmentioning
confidence: 99%
“…Dobutamine was infused intravenously using a mechanical pump, starting at the dose of 5 jig/kg per minute for 3 minutes, increasing by 5 ug/kg per minute at 3-minute intervals to a maximal rate of 40 ,ug/kg per minute administered over 5 minutes. Dipyridamole was infused intravenously at the dose of 0.56 mg/kg over 4 minutes, followed by 4 …”
Section: Stress Protocolsmentioning
confidence: 99%
“…Different examiners have different eyes, but there is excellent concordance between experienced observers after a limited learning curve.22) Therefore, qualitative image analysis of wall motion remains the current standard with minimal interobserver variability . 23,24) CLINICAL IMPLICATIONS This study indicates that intraoperative transesophageal echocardiography with NTG appears to be a safe, noninvasive, feasible, cost-effective and widely available method to identify myocardial viability under the condition supported …”
Section: Discussionmentioning
confidence: 99%
“…During the pre-digital era, promising results had been achieved, but difficult technical problems made it hard to use the method. Armstrong and Feigenbaum [46] were pioneers in the field of digital computerized technology. In studies where men have predominated, a sensitivity of between 61 and 86% has been found, in addition to a high specificity of 75-100%.…”
Section: Diagnosticsmentioning
confidence: 99%